Clinical efficacy of aloe vera based products available in the market as skin moisturiser measured by tewl value and skin hydration level by using dermalab technology - Wan Sulaiman, Wan Mohd. Azizi; Azad, Abul Kalam; Ahmad, Nazia A.; Sunzida, Nushrat Khan (SILAE (Italo-Latin American Society of Ethnomedicine), 2016)
This study was conducted to evaluate the efficacy of Aloe Vera as skin moisturizer as measured by Trans Epidermal Water Loss (TEWL) and hydration value. The Dermalab®Combo was used to determine the efficacy of skin cosmetic products. Fifteen subjects were divided into three groups where each group was tested with one type of moisturizer product available in the local market. The TEWL and Hydration level of the subjects were measured before they were treated with the products as the baseline reading and after 3 weeks applying the products twice daily on the left forearm. The TEWL and Hydration levels were increased after 3 weeks for both side but the percentage increment of TEWL on the test side was lower than control side. Meanwhile, the percentage increment of Hydration level was higher on the test side compare to the control side. From the results, it is clear that Aloe Vera is effective for skin care treatment. In conclusion, it can be used as ingredient to improve skin barrier function for different skin care products formulations.